Research of Three Dimensional Transient Temperature Rise Characteristic of Wet Brake - Cui Tingqiong; Fan Jianwen; Jing Suping; Yang Lei (Jixie chuandong)
Aiming at the thermal fatigue problem of off-road vehicles under continuous braking,a three-dimensional transient thermal-mechanical coupling analysis model of wet brake is established,the influence of thermal boundary on the temperature rise are considered,such as heat flux,heat flux distribution coefficient and convective heat transfer coefficient. By using finite element analysis software ANSYS,the changing situation of wet brake disc of off-road vehicles in the continuous braking process is simulated,the distribution of disc temperature field and stress field are obtained. The results show that the temperature distribution in the middle of the contact interface radius is uneven,which is easy to produce thermal fatigue. The stress concentration is obvious in the place where the temperature gradient is large. The analysis result is consistent with the actual situation,which provides the theoretical basis for the design of wet brake.